Implementasi Metode Certainty Factor Untuk Mendiagnosa Kondisi Psikis Siswa-Siswi SMA Dalam Menghadapi Ujian Nasional Berbasis Komputer (UNBK) - Cindy Shintia Afriani Harahap; Bosker Sinaga (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2020)
Now that online-based exams are starting to take effect, every school in Indonesia takes the computer-based national exams (UNBK) where this UNBK can cause psychological problems for class XII students who will face it. There are 4 types of psychological disorders, namely psychological responses to constraints and demands, physical responses, perceptual responses and physical responses. To reduce the psychological disorders experienced by students, this study uses an expert system using the certainty factor method. The goal is to find out the psychological condition of students and what solutions should be given. This research is correlational quantitative. This study used a research subject of 115 students taken from some of the students of class XII SMA Negeri 2 Perbaungan using random sampling techniques. This research draws data from 2019. Through this system, counseling teachers can manipulate disease data, symptoms and solutions. In this system, applying the certainty factor method to expert systems with the stages of system requirements, system design and software, system testing implementation. Based on the results of data analysis, it was found that there were psychological disorders with perceptual responses of 0.99 and physical responses of 0.99.